Phylogenomic analysis and revised classification of atypoid mygalomorph spiders (Araneae, Mygalomorphae), with notes on arachnid ultraconserved element loci - Hedin, Marshal; Derkarabetian, Shahan; Alfaro, Adan; Ramírez, Martín J.; Bond, Jason E. (PeerJ, 2019)
The atypoid mygalomorphs include spiders from three described families that build a diverse array of entrance web constructs, including funnel-and-sheet webs, purse webs, trapdoors, turrets and silken collars. Molecular phylogenetic analyses have generally supported the monophyly of Atypoidea, but prior studies have not sampled all relevant taxa. Here we generated a dataset of ultraconserved element loci for all described atypoid genera, including taxa (Mecicobothrium and Hexurella) key to understanding familial monophyly, divergence times, and patterns of entrance web evolution. We show that the conserved regions of the arachnid UCE probe set target exons, such that it should be possible to combine UCE and transcriptome datasets in arachnids. We also show that different UCE probes sometimes target the same protein, and under the matching parameters used here show that UCE alignments sometimes include non-orthologs. Using multiple curated phylogenomic matrices we recover a monophyletic Atypoidea, and reveal that the family Mecicobothriidae comprises four separate and divergent lineages. Fossil-calibrated divergence time analyses suggest ancient Triassic (or older) origins for several relictual atypoid lineages, with late Cretaceous/early Tertiary divergences within some genera indicating a high potential for cryptic species diversity. The ancestral entrance web construct for atypoids, and all mygalomorphs, is reconstructed as a funnel-and-sheet web.
Keywords: Spider; Phylogenomics; Ultraconserved element; Orthology; Web evolution; Mygalomorphae; Taxonomy; Cryptic species; Exons